Postoperative delirium in patients with head and neck oral cancer in the West of Scotland. Issue 3 (April 2021) - Crawford, J.E.; Zubair, F.; Baniulyte, G.; Wales, C.J.; Ansell, M.; Thomson, E.; Hislop, S.; MacIver, C.; Devine, J.; McCaul, J.; Young, D.; McMahon, J.
Abstract: Our aims were to determine the prevalence and association of postoperative delirium (POD) in head and neck (H&N) cancer patients undergoing free flap reconstruction at the oral and maxillofacial surgery (OMFS) unit, Queen Elizabeth University Hospital (QEUH) Glasgow, and to assess whether these determinants can be modified to optimise patient care and reduce the occurrence of POD. Delirium remains an important problem in the postoperative care of patients undergoing major H&N surgery, and early detection and management improve overall outcomes. The patient database containing details of the preoperative physical status (including alcohol misuse, chronic comorbidity, and physiological status) of 1006 patients who underwent major H&N surgery with free-flap repair at the QEUH from 2009-2019, was analysed. Factors associated with delirium were studied, identifying univariate associations as well as multivariate models to determine independent risk factors. The incidence of POD was 7.5% (75/1006; 53 male:22 female; mean (SD) age 65.41 (13.16) years). POD was strongly associated with pre-existing medical comorbidities, excess alcohol, smoking, a prolonged surgical operating time (more than 700 minutes), tracheostomy, blood transfusion, and bony free flaps. Those with POD were at an increased risk of postoperative wound and lung complications, and were more likely to require a hospital stay of more than 21 days. Presurgical assessment should identify risk factors to optimise the diagnosis and treatment of POD, and will enhance patient care by reducing further medical and surgical complications, and overall hospital stay.